2020
DOI: 10.1016/j.copbio.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Simplified monomeric VHH-Fc antibodies provide new opportunities for passive immunization

Abstract: Simplified monomeric monoclonal antibodies consisting of a single-domain VHH, derived from camelid heavy-chain only antibodies, fused with the Fc domain of either IgG (VHH-IgG) or IgA (VHH-IgA) antibodies, are promising therapeutic proteins. These simplified single-gene encoded antibodies are much easier to manufacture and for bulk applications can be produced in plants and in yeast. These merits enabling novel passive immunization applications, such as in-feed oral delivery of VHH-IgA, which successfully prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Although the market consists predominantly of IgG subtype Fc fusions, there has been much interest in developing an alternative IgA-based Fc scaffold for the control of mucosal pathogens in applications such as oral passive immunization Bakema and Van Egmond, 2011;Lohse et al, 2011;De Greve et al, 2020). Unlike the IgG Fc, the IgA Fc assembles with two other subunits, a 15 kDa joining chain (JC) and a 70 kDa secretory component (SC), to form a secretory complex (sIgA) (Supplementary Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the market consists predominantly of IgG subtype Fc fusions, there has been much interest in developing an alternative IgA-based Fc scaffold for the control of mucosal pathogens in applications such as oral passive immunization Bakema and Van Egmond, 2011;Lohse et al, 2011;De Greve et al, 2020). Unlike the IgG Fc, the IgA Fc assembles with two other subunits, a 15 kDa joining chain (JC) and a 70 kDa secretory component (SC), to form a secretory complex (sIgA) (Supplementary Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…We subsequently showed that these chimeric fusions neutralize a 4th EHEC serotype, O145 (Chin-Fatt, unpublished). Simplified chimeric V H H-IgA Fc, which involve replacing the Fab region with a V H H, are much easier to produce and are encoded by a single gene, rather than four required for full sized sIgA (De Greve et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional Igs used in passive immunization include IgG for intravenous injection and IgA for intestinal tract. Their production involves heavy chain and light chain expression and correct assembly, and the genes encoding J-chain and secretory component are also required for secretory IgA (SIgA), which is very complex and challenging (De Greve et al 2020 ). Nanobodies can be grafted on to the Fc domain of Immunoglobulin (IgG or IgA) at the hinge region to make monomeric nanobody-Fc antibodies, which are easy to manufacture because they are encoded by a single gene (De Greve et al 2020 ).…”
Section: Nanobody Expression In Plantsmentioning
confidence: 99%
“…Their production involves heavy chain and light chain expression and correct assembly, and the genes encoding J-chain and secretory component are also required for secretory IgA (SIgA), which is very complex and challenging (De Greve et al 2020 ). Nanobodies can be grafted on to the Fc domain of Immunoglobulin (IgG or IgA) at the hinge region to make monomeric nanobody-Fc antibodies, which are easy to manufacture because they are encoded by a single gene (De Greve et al 2020 ). Fc domain fusion extends their circulatory half-life to avoid rapid clearance from host (Hutt et al 2012 ), and is proved to be capable of boosting the nanobody-Fc protein accumulation levels in Arabidopsis seeds (De Buck et al 2013 ).…”
Section: Nanobody Expression In Plantsmentioning
confidence: 99%
See 1 more Smart Citation